EJECTION FRACTION: THE TOP OF AN ICEBERG - Yabluchansky, N.I. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
The work was focused on problems of clinical application of ejection fraction. It was proved that ejection fraction may be used in diagnostics only within a complex of other indices of circulation system.